Cellular milieu in clear cell renal cell carcinoma - Raghubar, Arti M.; Roberts, Matthew J.; Wood, Simon; Healy, Helen G.; Kassianos, Andrew J.; Mallett, Andrew J. (Frontiers in Oncology, 2022)
Clear cell renal cell carcinoma (ccRCC) is globally the most prevalent urological cancer. The cells of origin in ccRCC have been identified as proximal tubular epithelial cells (PTEC) however, the transcriptomic pathways resulting in the transition from normal to malignant PTEC state has remained unclear. An enriched immune cell infiltrate is a recognized characteristic of ccRCC that has gained attention due to available immune checkpoint therapies however, a sustained clinical response has been limited for ccRCC patients. This indicates that our understanding of the mechanisms involved in the malignant transition and resistance to immune checkpoint therapy in ccRCC is unclear. This Review examines recent single cell transcriptomic studies of ccRCC to clarify the transition of PTEC in ccRCC development; the immune cell types, states and interactions that may limit response to targeted immune therapy and finally suggests stromal cells as key drivers in recurrent and locally invasive ccRCC. These and future single cell transcriptomic studies will continue to clarify the cellular milieu in ccRCC microenvironment thus defining actional clinical, therapeutic and prognostic characteristics of ccRCC.